1987
DOI: 10.1177/001872088702900306
|View full text |Cite
|
Sign up to set email alerts
|

Hesitations in Continuous Tracking Induced by a Concurrent Discrete Task

Abstract: Subjects performed continuous, visually guided pursuit tracking with the right hand while giving simultaneous discrete left-hand responses, which were signaled by auditory tones appearing at the average rate of one tone per 30 s. This left-hand secondary task was frequently associated with tracking hesitations lasting 333 ms or longer. The rate of occurrence of these hesitations was about the same when the left-hand response involved a choice between competing responses as when the left hand responded in a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
1

Year Published

1993
1993
2001
2001

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 11 publications
3
36
1
Order By: Relevance
“…Klapp et al (1987) found the frequency of tracking holds and holds of long duration to decrease with increased tracking priority. Tsang and Wickens (1988) found that subjects were better able to protect the primary task in the manual-manual task pairs than in the manual-speech task pairs from error spikes, despite a greater level of interference (larger dual-task performance decrement) in the manual-manual task pairs.…”
Section: Causes Ofinterferencementioning
confidence: 97%
See 3 more Smart Citations
“…Klapp et al (1987) found the frequency of tracking holds and holds of long duration to decrease with increased tracking priority. Tsang and Wickens (1988) found that subjects were better able to protect the primary task in the manual-manual task pairs than in the manual-speech task pairs from error spikes, despite a greater level of interference (larger dual-task performance decrement) in the manual-manual task pairs.…”
Section: Causes Ofinterferencementioning
confidence: 97%
“…Yet, they all reported clear dual-task interference, provided that the tasks were sufficiently difficult (Cliff, 1973;Tsang & Wickens, 1988;Vidulich, 1990). Interference was observed between two visual tasks (Fracker & Wickens, 1989;Onstott, 1976;Tsang & Wickens, 1988;Vidulich, 1989Vidulich, , 1990, between one visual and one auditory task (Cliff, 1973;Klapp et al, 1987;McLeod, 1977;Netick & Klapp, 1994;Tsang & Wickens, 1988), between two tracking axes controlled by the same hand (Onstott, 1976), between two tasks controlled by two hands (Fracker & Wickens, 1989;Klapp et al, 1987;McLeod, 1977;Netick & Klapp, 1994;Tsang & Wickens, 1988;Vidulich, 1989Vidulich, , 1990, and between two tasks, one controlled manually and one by speech (Cliff, 1973;Tsang & Wickens, 1988). It would be difficult to attribute all of these interferences to peripheral interference due to performing two tasks of the same input modality, of the same output modality, or with the same physical apparatus.…”
Section: Dual-task Interferencementioning
confidence: 97%
See 2 more Smart Citations
“…Interference could result from costs of concurrence (Navon and Gopher 1979), that is, the effort of time-sharing per se or from a competition for control of peripheral inputs and/ or outputs (e.g., Klapp et al 1987). Compelling evidence for a role of resource competition was provided only by one study, which used two levels of LT difficulty (Kramer and Strayer 1988), and two studies that included a nonlearning control for AT (Trumbo et al 1968;Hazeltine et al 1997): Either manipulation should have no effect on time sharing or on peripheral competition; however, both altered the magnitude of dual-task interference, thus supporting the role of resource competition.…”
mentioning
confidence: 99%